Lack of carcinogenicity of daminozide, alone or in combination with its contaminant 1,1-dimethylhydrazine, in a medium-term bioassay - Cabral, R; Hakoi, K; Hoshiya, T; Hasegawa, R; Ito, N (Teratogenesis, carcinogenesis, and mutagenesis, 1995)
The carcinogenicity of daminozide (succinic acid-2,2-dimethylhydrazide; Alar), a plant growth regulator used primarily in apple orchards, has been the subject of recent investigations by several national and international organizations because of contradictory study results. The aim of the present study was to assess the carcinogenicity of daminozide alone and in combination with 1,1-dimethylhydrazine (UDMH), its major contaminant, in a novel medium-term bioassay in Fischer 344 rats, the DEN-PH model. Rats were given diethylnitrosamine (DEN) at 200 mg/kg body weight intraperitoneally and then 2 weeks later were given daminozide at 20,000 ppm or daminozide plus UDMH at 75, 150, or 300 ppm in the diet for 6 weeks and were then killed; all rats underwent a partial (two-thirds) hepatectomy (PH) at week 3. Hepatocarcinogenic potential was assessed by comparing the number and area of preneoplastic foci positive for the glutathione S-transferase placental form (GST-P+) in the liver of treated rats, with those in controls given DEN alone. Daminozide, UDMH, and the combination were not carcinogenic in this model. This novel medium-term bioassay for carcinogenicity is considered to be practical for the rapid evaluation of both agrochemical formulations and contaminants found in agrochemicals and other compounds.